Sense of humour as a pedagogical resource: Towards a didactics of didactics - Fernández-Solís, Jesús Damián (Pulso. Revista de educación, 2003)
The article begins by discussing my interest in the educational potential of humour. It then proceeds to present the theoretical foundation of the Pedagogy of Humour as a socio-educational intervention proposal. The second part provides an overview of the workshops and courses on this topic that I have conducted. I explain the importance of specific training in the Pedagogy of Humour, outline the objectives of the workshops, and numerically bullet point the contents and methodology used. I share a specific experience with university professors and identify the target audience and institutions interested in the subject and identify the target audience and institutions interested in the subject. I conclude with a brief assessment of the training experience.